2008
DOI: 10.1002/cd.217
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing multidimensional identity negotiation: Reflections on the lived experiences of first-generation college students

Abstract: Drawing from recent research on first-generation college (FGC) students, this chapter advances an interdisciplinary theoretical framework for understanding how these students enact multiple aspects of their personal, cultural, and social identities. I use dialectical and cross-cultural adaptation theories as a foundation to extend examinations of how diverse FGC students negotiate the alien culture of the academy against that of home. In this regard, college is situated as a pivotal point of development, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 10 publications
(15 reference statements)
1
67
0
Order By: Relevance
“…As FGC students transition from high school to college, they begin to establish an identity apart from their family (Orbe, 2008). However, they still remain linked to their family since their success remains a part of family pride and success (Orbe, 2003(Orbe, , 2008.…”
Section: First-generation College Studentsmentioning
confidence: 98%
“…As FGC students transition from high school to college, they begin to establish an identity apart from their family (Orbe, 2008). However, they still remain linked to their family since their success remains a part of family pride and success (Orbe, 2003(Orbe, , 2008.…”
Section: First-generation College Studentsmentioning
confidence: 98%
“…Another more peripheral (to dialectics) study examined the turning points and dialectical interpretations of first generation college (FGC) student experiences in the United States (Orbe, 2008). Using interview and questionnaire data, Orbe employs the dialectic as a way to understand the complex ways in which FGC students negotiate and perform multiple aspects of their identities.…”
Section: The Six Dialectics As a Framework For Studying Interculturalmentioning
confidence: 99%
“…Correspondingly, in Lehmann's (2007) qualitative study, first-generation students reported not fitting in, not able to relate to more affluent students with college educated parents, and not persisting to graduation despite solid academic performance. Additionally, Orbe (2008) believed two of the primary tensions: individual versus social identity and stability versus change identity were particularly important in understanding the experiences of first-generation students.…”
Section: Characteristics Of First-generation and Low-income College Smentioning
confidence: 99%
“…Firstgeneration status can often be overlooked and is not as visible a status as race or gender, but can be an equally challenging identity in certain environments. In regard to firstgeneration status, Orbe (2008) stated: "making this aspect of his or her identity known to others may result in (mis) perceptions that the student is ill prepared for college-level academics, without substantial educational aspirations, socially or communicatively inept, and less committed to participating fully in the learning process" (p. 92).…”
Section: Obstacles Challenges and The Importance Of Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation